HP0009 Audit of a rheumatology nurse specialist (rns) shoulder injection clinic. (1st June 2001) - Pointer, WD; Williams, PL
Abstract : In order to shorten waiting times for referrals for shoulder pain, we have set up a dedicated clinic, run by a RNS trained in assessment and management of shoulder problems, including injection of corticosteroid, to which all consecutive new patients, who were thought likely from the letter of referral to benefit from an injection were allocated. Diagnosis was discussed and confirmed with the Rheumatologist. The results of the first 56 patients (23 male) to attend have been audited. Diagnosis was as follows: Adhesive Capsulitis 21, Supraspinatus Tendonitis 11, Rotator Cuff Lesion 7, Non-specific shoulder pain 5, Occupation related shoulder pain 3, Bicipital Tendonitis 3, Thoracic outlet compression 1, Acromioclavicular joint pain 1, Posture related shoulder pain 1, Fibromyalgia 1, Referred pain from hepatic secondaries 1, Secondary deposit 1. In 18 patients (32%) the clinic and GP diagnoses were the same. In 16 (28.6%) they differed and in 22 (37.5%) the GP letter indicated painful shoulder but no specific diagnosis. Of these patients 36 (64%) were treated with injection. The remaining 20 (36%) were not injected for the following reasons: Symptoms resolved 12, Patient declined 3, Inappropriate 4, Reason not recorded 1. Of the 56 patients audited, 49 were available for review by telephone at a minimum of 3 months after initial visit. The results of this interview showed that 17 had complete resolution of symptoms, 21 had more than 50% improvement, 1 less than 50% improvement, 5 said their symptoms were unchanged and 5 stated their symptoms were worse. Conclusion: A RNS shoulder injection clinic works well but the range of possible diagnoses requires close collaboration with the Rheumatologist.